(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Sports anxiety affects athletes¢bodies that are led by eye abilities and the quality of visual information for performance. This study aimed to identify the sports anxiety and the level of horizontal peripheral visual ability of girl goalkeepers. The study was applied on a sample of (14) goalkeepers out of (16) who participated in the Syrian Women’s league 2019/2020. The study was applied to football studioms in the governorates of Syria. The study used the descriptive approach and the sports anxiety questionnaire which was designed by (KAFAFY, et al., 1985) and a test to measure horizontal peripheral visual ability due to its agreeability to the nature of this research. The arithmetic mean and the Pearson correlation coefficient were used to find out the correlation between mathematical anxiety and horizontal peripheral visual ability. Through the results, it was concluded that there is no significant correlation between the variables of sports anxiety and horizontal peripheral visual ability.